Factors related to childbirth self-efficacy among primigravida in Yogyakarta - Muafiqoh Dwiarini (Alma Ata University Press, 2022)
Background : Childbirth self-efficacy refers to a woman's self-confidence in herability to cope with labor and contributes significantly to her perception of pain during labor. Mothers with low self-efficacy felt nervous, felt they lacked strength, and expressed more fear, so that the labor process did not go smoothly and lasted longer, causing greater pain for both the mother and baby. Pregnant women with high childbirth self-efficacy had higher intention to attempt vaginal birth, while those choosing caesarean had lower self-efficacy beliefs. Objectives : This study was to determine factors related childbirth self-efficacy among primigravida. Methods : This study used analytic observational method with cross sectional design. This research was conducted at Community Health Centers and two maternity clinics in Yogyakarta with 112 sample pregnant woman. They were recruited using a purposive sampling technique based on the criteria. The study used Childbirth Self-Efficacy (CBSEI) scale, the Fear of Childbirth (FOC) scale, and demographic data questionnaires. The independent sample t-test, ANOVA, pearson’s correlation coefficient, to determine the factors related childbirth self-efficacy. Results : The results of this study indicate that the factors associated with childbirth self-efficacy were antenatal class and prenatal yoga with a p value of 0.000 (p <0.05). In addition, there is a significant negative correlation between childbirth self-efficacy and fear of childbirth (r = -.34, p < .01). In other words, pregnant women with higher childbirth self-efficacy meant less fear of childbirth.Conclusions: Factors related childbirth self-efficacy were antenatal class, prenatal yoga, and fear of childbirth. The results of this study provided a better understanding of factors related childbirth self-efficacy. Based on the results, strategies to increase childbirth self-efficacy should focus on decreasing the level of fear of childbirth, which can be done by attending prenatal education and doing prenatal yoga.